Does black-hole growth depend on the cosmic environment?. Issue 1 (19th July 2018) - Yang(杨光), G; Brandt, W N; Darvish, B; Chen(陳建廷), C-T J; Vito, F; Alexander, D M; Bauer, F E; Trump, J R
ABSTRACT: It is well known that environment affects galaxy evolution, which is broadly related to supermassive black hole (SMBH) growth. We investigate whether SMBH evolution also depends on host-galaxy local (sub-Mpc) and global (≈1–10 Mpc) environment. We construct the surface-density field (local environment) and cosmic web (global environment) in the Cosmic Evolution Survey (COSMOS) field at z = 0.3–3.0. The environments in COSMOS range from the field to clusters ( M halo ≲ 10 14 M⊙ ), covering the environments where ≈\!99 per cent of galaxies in the Universe reside. We measure sample-averaged SMBH accretion rate (BHAR ) from X-ray observations, and study its dependence on overdensity and cosmic-web environment at different redshifts while controlling for galaxy stellar mass ( M ⋆ ). Our results show that BHAR does not significantly depend on overdensity or cosmic-web environment once M ⋆ is controlled, indicating that environment-related physical mechanisms (e.g. tidal interaction and ram-pressure stripping) might not significantly affect SMBH growth. We find that BHAR is strongly related to host-galaxy M ⋆, regardless of environment.